Influencia de sistemas de siembra y arreglos de asociación en el rendimiento de las especies maíz (Zea mays L.), fríjol (Phaseolus vulgaris L.), haba (Vicia faba L.), arveja (Pisum sativum L.). - Novoa Parrado, José Manuel; Rivera Rodríguez, José Benjamín. (Universidad Nacional de Colombia, 2018)
Arveja-Pisum sativum